MANAJEMEN SEKOLAH BERBASIS NILAI-NILAI KEARIFAN LOKAL TRI HITA KARANA TERHADAP KINERJA GURU - Putu Cory Candra Yhani (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2017)
Quality education can produce quality and productive human resources (HR). The quality of education is determined by the achievement of the organizers and the implementation of the educational objectives. With guaranteed quality and highly productive human resources, Indonesia will be able and ready to face the challenges of the world. Achieving educational goals and objectives of educational institutions in particular can not be separated from the human element and non-human elements. Therefore, the performance shown by these elements will show the ability of educational organizations in achieving predetermined goals. As education staff, teachers will always be demanded about the extent to which teachers' teaching performance in carrying out and completing their work, whether they are performing well or poorly. Thus, a teacher in the work assessment by the principal is always associated with work performance and satisfaction.Keyword: Tri Hita Karana School Management and Teacher Performance